Lithium ion battery

The lithium-ion battery with protrusions and depressions on the positive electrode, along with carboxylic acid esters and nitrile compounds, addresses lithium plating during fast charging, enhancing battery performance and safety.

CN119208517AActive Publication Date: 2024-12-27ZHUHAI COSMX BATTERY CO LTD

Patent Information

Application Number
CN202411723649.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2024-12-27
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

Fast charging of lithium-ion batteries leads to lithium plating on the negative electrode, reducing battery life and posing safety risks due to overheating and expansion.

Method used

A lithium-ion battery design featuring protrusions and depressions on the positive electrode sheet, combined with a specific ratio of carboxylic acid esters and nitrile compounds in the electrolyte, enhances electrode liquid storage, optimizes lithium ion transmission, and improves conductivity, thereby reducing lithium plating.

Benefits of technology

The design increases electrode liquid storage space, optimizes lithium ion transmission, and improves fast charging performance and cycle stability by reducing lithium plating and associated safety issues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208517A_ABST
    Figure CN119208517A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, and provides a lithium ion battery. In the lithium ion battery, in the thickness direction of a positive plate, the positive plate comprises a first surface and a second surface which are oppositely arranged, a plurality of first convex parts are arranged on the first surface at intervals, and a plurality of first concave parts are correspondingly arranged on the second surface; the height of the first protruding part is recorded as H [mu] m, the diameter of the first protruding part is recorded as R mm, and H / R is larger than or equal to 0.2 and smaller than or equal to 80; the electrolyte comprises carboxylic ester, and based on the total mass of the electrolyte, the mass ratio of the carboxylic ester is marked as A; a satisfies 10 < = A < = 80; the electrolyte comprises a nitrile compound, and based on the total mass of the electrolyte, the mass ratio of the nitrile compound is marked as B; b satisfies 3 < = B < = 30. When the conditions are met, the quick charge performance of the battery can be improved, and the cycle stability of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery. Background Art

[0002] Lithium batteries have become an indispensable part of human daily life. They provide long-lasting and powerful power for smartphones, laptops, electric vehicles, etc. Whether at work, study or entertainment, the convenience and reliability of lithium batteries have greatly improved the quality of life. With the advancement of technology, fast charging technology has emerged, which greatly shortens the charging time and meets the needs of modern people's fast-paced life.

[0003] However, during the fast charging process, a problem that needs to be solved is the lithium plating phenomenon. When lithium ions are quickly deintercalated from the positive electrode and try to be embedded in the negative electrode, if the embedding speed of the negative electrode cannot keep up with the charging speed, or the surface of the electrode is saturated with lithium, lithium ions will be deposited on the surface of the negative electrode to form metallic lithium. This will not only reduce the service life of the battery, but may also cause safety problems such as battery overheating, expansion, and even fire. Therefore, how to effectively control and avoid lithium plating while increasing the charging speed has become an important issue in the development of lithium battery technology. Summary of the invention

[0004] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art and to provide a lithium-ion battery, wherein a protrusion and a depression are arranged on the positive electrode sheet, and by controlling the proportional relationship between the height of the protrusion and the diameter of the protrusion, an uneven texture of suitable size can be formed on the surface of the positive electrode sheet, which can increase the electrode liquid storage space, optimize the lithium ion transmission path, and improve the fast charging performance of the battery; at the same time, the carboxylic acid ester and nitrile compounds introduced into the electrolyte have a lower viscosity, which can improve the conductivity and accelerate the uniform transmission rate of lithium ions, effectively alleviating the problem of uneven local lithium ion transmission rate that may be caused by the protrusions and depressions on the electrode sheet, reducing lithium plating and improving the battery cycle stability.

[0005] In order to achieve the above object, the present invention provides a lithium ion battery, the battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte; In the thickness direction of the positive electrode sheet, the positive electrode sheet includes a first surface and a second surface arranged opposite to each other, the first surface is provided with a plurality of first protrusions at intervals, and the second surface is provided with a plurality of first recesses correspondingly; the height of the first protrusion is recorded as H μm, the diameter of the first protrusion is recorded as R mm, and H and R satisfy: 0.2≤H / R≤80; The electrolyte includes carboxylic acid ester, and the mass proportion of the carboxylic acid ester is denoted as A% based on the total mass of the electrolyte; A satisfies: 10≤A≤80; The electrolyte includes a nitrile compound, and the mass proportion of the nitrile compound, based on the total mass of the electrolyte, is denoted as B%; B satisfies: 3≤B≤30.

[0006] The present invention adopts the above technical solution to achieve the following beneficial effects: The lithium-ion battery provided by the present invention forms an uneven texture of appropriate size on the surface of the positive electrode sheet by adjusting the ratio of the height of the protrusion to the diameter of the protrusion, thereby increasing the electrode liquid storage space, optimizing the lithium ion transmission path, and improving the fast charging performance; at the same time, the carboxylic acid ester and nitrile compounds introduced into the electrolyte reduce the viscosity, improve the conductivity, accelerate the uniform transmission rate of lithium ions, effectively alleviate the problem of uneven local lithium ion transmission rate that may be caused by setting protrusions and recessed portions on the electrode sheet, reduce lithium plating, and improve the battery cycle stability.

[0007] The endpoints and any values ​​of the range disclosed in this article are not limited to the precise range or value, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Herein, in the absence of special instructions, data ranges include endpoints. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] Figure 1 Shown is a structural schematic diagram of a positive electrode sheet in an embodiment of the present invention.

[0009] Figure numerals: 1, positive electrode current collector; 2, positive electrode active material; 3, second surface; 4, first surface; 5, first recessed portion; 6, first protruding portion. DETAILED DESCRIPTION

[0010] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0011] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.

[0012] In the present invention, the terms "battery", "lithium battery", "lithium-ion battery" and "lithium-ion secondary battery" all have the same meaning and refer to lithium-ion secondary batteries, which generally include an electrode assembly (such as a positive electrode sheet, a negative electrode sheet and a separator), a container (shell) for accommodating the electrode assembly, and an electrolyte.

[0013] In the present invention, the term "C4-C10 carboxylate" refers to a carboxylate in which the number of carbon atoms in the hydrocarbon group (i.e., the carbon chain connected to the carboxyl group) in the carboxylate molecule is between 4 and 10.

[0014] In the present invention, the term "fluorocarboxylate" refers to a compound formed when the hydrogen atom in the carboxylate molecule is replaced by a fluorine atom, wherein when the fluorinated derivative of C4-C10 carboxylate is a fluorocarboxylate, it refers to a compound formed when the hydrogen atom in the C4-C10 carboxylate is replaced by a fluorine atom.

[0015] In the present invention, the term "C2-C10 mononitrile compound and its fluorinated derivative" refers to a nitrile compound containing only one cyano group and having a carbon number between 2 and 10. "Fluorinated derivative of C2-C10 mononitrile compound" refers to a compound formed by replacing a hydrogen atom in a hydrocarbon group of a mononitrile compound having a carbon number between 2 and 10 with a fluorine atom. The mononitrile compound and its fluorinated derivative include saturated mononitrile compounds and their fluorinated derivatives, and also include unsaturated mononitrile compounds and their fluorinated derivatives.

[0016] In the present invention, the term "C2-C10 polynitrile compounds and fluorinated derivatives thereof" refers to nitrile compounds containing two or more cyano groups and having carbon atoms between 2 and 10. "Fluorinated derivatives of C2-C10 polynitrile compounds" refers to compounds formed by replacing hydrogen atoms in the hydrocarbon groups of polynitrile compounds having carbon atoms between 2 and 10 with fluorine atoms. Among them, polynitrile compounds and fluorinated derivatives thereof include saturated polynitrile compounds and fluorinated derivatives thereof, and also include unsaturated polynitrile compounds and fluorinated derivatives thereof.

[0017] The present invention provides a lithium ion battery, the battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte; In the thickness direction of the positive electrode sheet, the positive electrode sheet includes a first surface and a second surface arranged opposite to each other, the first surface is provided with a plurality of first protrusions at intervals, and the second surface is provided with a plurality of first recesses correspondingly; the height of the first protrusion is recorded as H μm, the diameter of the first protrusion is recorded as R mm, and H and R satisfy: 0.2≤H / R≤80; The electrolyte includes carboxylic acid ester, and the mass proportion of the carboxylic acid ester is denoted as A% based on the total mass of the electrolyte; A satisfies: 10≤A≤80; The electrolyte includes a nitrile compound, and the mass proportion of the nitrile compound, based on the total mass of the electrolyte, is denoted as B%; B satisfies: 3≤B≤30.

[0018] Exemplarily, the value of H / R can be 0.2, 0.3, 0.4, 0.5, 0.75, 1, 3, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80 or any point value in the range consisting of any two of the above points.

[0019] Illustratively, in the electrolyte, the mass proportion A% of the carboxylic acid ester can be, for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or any point value in the range consisting of any two of the above point values.

[0020] Exemplarily, in the electrolyte, the mass proportion B% of the nitrile compound can be, for example, 3%, 5%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30% or any point value in the range consisting of any two of the above point values.

[0021] It should be noted that when calculating the value of the formula H / R, H and R are substituted into the formula with corresponding values, without considering the conversion of units. For example, when H=20 μm and R=2 mm, H / R=20 / 2=10; During the charge and discharge process of the battery, the embedding and release process of lithium ions in the electrode will cause a large volume change inside the battery. This volume change makes the electrode surface bear a greater extrusion pressure. The electrode surface in the arc part of the winding structure of the wound battery receives a greater extrusion pressure, which is more likely to deform, easily leading to insufficient electrolyte in the arc part. The transmission channel of lithium ions is restricted, resulting in the inability of lithium ions to smoothly reach the negative electrode surface for embedding, thereby causing safety problems such as lithium plating.

[0022] The present invention arranges raised portions and recessed portions on the positive electrode sheet. Such uneven texture makes the surface of the electrode sheet have a certain gap structure. When subjected to extrusion pressure, the stress is released, thereby stabilizing the internal structure of the electrode sheet. The recessed portion formed by the electrode sheet and the space formed by the raised portion and the diaphragm can store electrolyte, providing a relatively stable storage space for the electrolyte, avoiding the problem of insufficient electrolyte at the stress concentration point of the electrode sheet, facilitating the normal conduction and transportation of lithium ions, and reducing the occurrence of lithium precipitation problems. In addition, the concave-convex texture formed on the surface of the positive electrode sheet increases the specific surface area of ​​the positive electrode sheet, and lithium ions have more transmission sites and paths to enter the interior of the electrode sheet, thereby increasing the transmission rate of lithium ions inside the electrode sheet, avoiding the accumulation of lithium ions on the surface of the electrode sheet during the fast charging process of the battery, thereby improving the fast charging performance of the battery. When forming the raised and recessed parts (such as rolling), tiny cracks will be generated on the surface of the positive electrode sheet. These cracks may cause the bending and rupture of the active material structure in the positive electrode sheet, which will cause the lithium ions to be unable to be smoothly deintercalated, resulting in a decrease in battery performance; in addition, it is easy to cause uneven compaction of the positive electrode sheet, which may lead to abnormal local lithium ion transmission rate and cause local lithium precipitation. Carboxylic acid esters and nitrile compounds are introduced into the electrolyte as solvent components. The electrolyte has a lower viscosity and a higher dielectric constant, which improves the conductivity of the electrolyte, accelerates the transmission rate of lithium ions, and avoids the large-scale aggregation of lithium ions at the same position after being released. At the same time, it will also accelerate the lithium ion transmission rate caused by the concentration difference, making the lithium ions more evenly distributed in the electrolyte and more evenly transmitted in the electrode sheet, effectively alleviating the problem of uneven local lithium ion transmission rate that may be caused by the formation of raised or recessed parts, so that the electrode surface has a good lithium ion transmission rate as a whole, reducing the local lithium precipitation of the embossed parts on the electrode surface, and improving the battery cycle stability.

[0023] In the present invention, by arranging protrusions and depressions on the electrode sheet and introducing carboxylic acid esters and nitrile compounds as solvents into the electrolyte, the problem of lithium plating during high-rate charge and discharge of the battery can be solved, lithium plating on the electrode surface can be reduced, thereby reducing problems such as battery capacity attenuation and battery volume expansion caused by lithium plating, and improving the fast-charging cycle stability of the battery.

[0024] In some embodiments, the height (H) of the first protrusion and the diameter (R) of the first protrusion are controlled to satisfy 0.2≤H / R≤80. When H / R>80, the raised structure (or embossed structure) of the positive electrode is relatively fragile and easily affected by mechanical stress, resulting in the embossed structure breaking. On the one hand, the active material structure inside the electrode may be damaged and deformed, affecting the normal embedding and extraction of lithium ions; on the other hand, during the battery cycle, the SEI film on the surface of the electrode may also be destroyed as the surface structure of the electrode deforms, resulting in a decrease in battery performance and possible safety problems; when H / R<0.2, the embossing degree is shallow, the embossed texture formed is not obvious, and there is no obvious difference between the embossed and unembossed parts. The problem of unstable electrode structure and insufficient electrolyte caused by stress extrusion cannot be effectively solved. At the same time, embossing does not significantly increase the specific surface area of ​​the electrode, and cannot increase the transmission rate of lithium ions between the electrolyte and the electrode, so it cannot play a role; preferably, when H and R satisfy 0.75≤H / R≤20, the mechanical strength of the raised and depressed parts can be taken into account, and the fast charging performance and safety of the battery can be better improved.

[0025] In some embodiments, Figure 1 As shown, the entire surface of the positive electrode sheet is embossed. In the thickness direction of the positive electrode sheet, the positive electrode sheet includes a second surface 3 and a first surface 4 that are arranged opposite to each other. After the second surface 3 is embossed, the positive electrode sheet forms a number of first recessed portions 5 that are evenly spaced, and the first surface 4 forms a number of first raised portions 6 that are evenly spaced corresponding to the first recessed portions 5. Similarly, after the first surface 4 is embossed, a number of first recessed portions 5 that are evenly spaced can be formed, and the second surface 3 forms a number of first raised portions 6 that are evenly spaced corresponding to the first recessed portions 5, that is, the positions of the first raised portions 6 and the first recessed portions 5 in the second surface 3 and the first surface 4 can be interchanged. The first raised portions or the first recessed portions can be evenly spaced, or unevenly spaced, preferably evenly spaced.

[0026] In some other embodiments, the embossing process may be performed only on a local area of ​​the positive electrode sheet, such as an edge area, an arc area, etc.

[0027] In some embodiments, the first raised portion or the first depressed portion (embossing pattern) is a regular or irregular shape, such as a circle, a square, a hexagon, other regular shapes or irregular shapes, preferably a regular shape, such as a circle.

[0028] In some embodiments, the first protrusions and the first recesses may be arranged in a uniform interval, or the arrangement may be adjusted according to actual needs, such as partially arranged in a uniform interval and partially arranged in a non-uniform interval.

[0029] In some embodiments, the first protrusion and / or the first depression satisfies at least one of the following conditions: (a) The average spacing between adjacent first protrusions or adjacent first recesses is denoted by D, and the average spacing between adjacent first protrusions (two adjacent first protrusions) is 0.5 mm-8 mm, for example, it can be 0.5 mm, 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm, 4.5 mm, 5 mm, 5.5 mm, 6 mm, 6.5 mm, 7 mm, 7.5 mm, 8 mm or any point value in the range composed of any two of the above point values, preferably 1 mm-4 mm; and / or, the average spacing between adjacent first recesses (two adjacent first recesses) is 0.5 mm-8 mm, for example, it can be 0.5 mm, 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm, 4.5 mm, 5 mm, 5.5 mm, 6 mm, 6.5 mm, 7 mm, 7.5 mm, 8 mm or any point value in the range composed of any two of the above point values, preferably 1 mm-4 mm. The average spacing between adjacent first protrusions and the average spacing between adjacent first depressions may be the same or different, preferably the same. The “average spacing between adjacent first protrusions” may be interpreted as the shortest straight distance between the edges of two adjacent and closest first protrusions on the surface of the positive electrode sheet in the length direction of the positive electrode sheet, such as Figure 1 As shown in D; "the average spacing between adjacent first recessed portions" can be interpreted as the shortest straight distance between the edges of two adjacent and closest first recessed portions on the surface of the positive electrode sheet in the length direction of the positive electrode sheet, such as Figure 1 As shown in D.

[0030] When the average spacing of the first protrusions and / or the average spacing of the first recessed portions meets the above range, the arrangement density of the first protrusions and / or the first recessed portions is within an appropriate range, and the number of the first protrusions and / or the first recessed portions is controlled within a certain area, which can not only ensure the effective improvement of the fast charging performance of the battery, but also avoid the problem of unstable positive electrode sheet structure caused by too small average spacing.

[0031] (b) The height of the first protrusion is denoted as H, and the height of the first protrusion can be 3 μm, 5 μm, 8 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm or any value in the range consisting of any two of the above values; and / or the depth of the first recess is 3 μm-100 μm, for example, can be 3 μm, 5 μm, 8 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm or any value in the range consisting of any two of the above values. The “height of the first protrusion” can be interpreted as the maximum distance from the top of the first protrusion away from the positive electrode current collector to the first surface of the positive electrode sheet; the “depth of the first concave portion” can be interpreted as the maximum distance from the bottom of the first concave portion close to the positive electrode current collector to the second surface of the positive electrode sheet, such as Figure 1 As shown in H. When the height of the first protrusion and / or the depth of the first recessed portion meet the above range, it can avoid the situation that the height of the first protrusion is too high or the depth of the first recessed portion is too deep, resulting in the structural fragility of the protrusion and the structural fragmentation caused by mechanical extrusion and wear; it can also avoid the situation that the height of the first protrusion is too low or the depth of the first recessed portion is too shallow, the electrolyte cannot well infiltrate the inside of the positive electrode sheet, and the improvement of the battery fast charging performance is not obvious.

[0032] (c) The diameter of the first protrusion is denoted as R, and the diameter of the first protrusion is 0.5 mm-4 mm, for example, it can be 0.5 mm, 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm or any point value in the range formed by any two of the above point values, preferably 1 mm-3 mm; and / or, the diameter of the first recessed portion is 0.5 mm-4 mm, for example, it can be 0.5 mm, 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm or any point value in the range formed by any two of the above point values, preferably 1 mm-3 mm. The "diameter of the first protrusion" or "diameter of the first recessed portion" can be interpreted as the maximum straight-line distance between the two edges of the first protrusion or the first recessed portion in the direction parallel to the positive electrode sheet, such as Figure 1 As shown in R. When the diameter of the first protrusion and / or the diameter of the first recessed portion meets the above range, the area of ​​the first protrusion and / or the first recessed portion can be controlled to avoid the weakening of the positive electrode sheet due to too large a diameter, which is prone to physical structural damage and causes the surface structure of the positive electrode sheet to break and the battery performance to deteriorate. It can also avoid the electrolyte being unable to infiltrate the inside of the positive electrode sheet well due to too small a diameter, which does not significantly improve the fast charging performance of the battery.

[0033] In some embodiments, the carboxylic acid ester includes at least one of C4-C10 carboxylic acid esters and fluorinated derivatives thereof. Preferably, the carboxylic acid ester includes at least one of ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, and difluoroethyl acetate.

[0034] In some embodiments, the nitrile compound includes at least one of a C2-C10 mononitrile compound and a fluorinated derivative thereof, a C2-C10 polynitrile compound and a fluorinated derivative thereof. Preferably, the nitrile compound includes at least one of acetonitrile, propionitrile, butyronitrile, isobutyronitrile, malononitrile, succinonitrile, glutaronitrile, adiponitrile, 1,3,6-hexanetrinitrile, benzonitrile, acrylonitrile, crotononitrile, trans-butenedinitrile, trans-hexenedinitrile, 1,2-bis(cyanoethoxy)ethane, and a fluorinated derivative thereof.

[0035] C4-C10 carboxylates have a low viscosity and a relatively high dielectric constant (viscosity ≤ 1mPa·s; dielectric constant ≥ 10); C2-C10 nitrile compounds have a moderate viscosity and a high dielectric constant (viscosity ≤ 2mPa·s; dielectric constant ≥ 20). When the above carboxylates and nitrile compounds are selected as solvents for the electrolyte, the viscosity of the electrolyte can be maintained at a low level, the conductivity of the electrolyte can be further improved, better kinetic properties can be obtained, the transmission rate of lithium ions in the electrolyte can be increased, and when the electrode is infiltrated, the problem of local lithium ion transmission rate differences in the electrode can be more effectively reduced, making the transmission of lithium ions more uniform, reducing local lithium plating of the battery, and further improving the fast charging performance and cycle safety of the battery.

[0036] In some embodiments, the carboxylic acid ester includes propyl propionate (PP) and difluoroethyl acetate (DFEA); in the electrolyte, the mass ratio of propyl propionate to difluoroethyl acetate is denoted as C, C satisfies: 1≤C≤10, and the value of C can be, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any point value in the range consisting of any two of the above point values. The fluorine atoms in DFEA have a high oxidation potential. When used as a solvent for the electrolyte, it can significantly improve the antioxidant properties of the electrolyte, allowing the electrolyte to exist stably during high-voltage cycling, thereby improving the battery's cycling performance under high voltage. However, DFEA has poorer solubility in lithium salts than other carboxylates. When the DFEA content is too high, it often leads to the precipitation of lithium salts, the electrolyte cannot maintain a uniform state, and the battery performance (such as cycling performance and safety) is significantly reduced. PP is a carboxylate, and the carboxyl group (-COOH) or ester group (-COO-) in its molecular structure can form a strong interaction with the lithium ions in the lithium salt, and has good solubility for the lithium salt. When PP is used in combination with DFEA, the solubility of the lithium salt can be improved, reducing problems such as lithium salt precipitation when DFEA is used alone, while improving the high-voltage cycling performance of the battery. When PP and DFEA are added to the electrolyte and recessed and raised portions are set on the pole piece, the uneven texture on the pole piece surface not only helps the electrolyte to be evenly distributed and quickly penetrate the pole piece, but also further optimizes the transmission performance of the electrolyte, helps the dissolution and transmission of lithium salts in the electrolyte, and to a certain extent alleviates the risk of lithium salt precipitation caused by high DFEA content, while enhancing the cycle stability and safety of the battery at high voltage. Therefore, the combination of PP and DFEA with recessed and raised portions set on the pole piece can jointly solve the problems of electrolyte inhomogeneity and lithium salt precipitation, while improving the high-voltage cycle performance of the battery.

[0037] In some embodiments, the fluorinated derivative of the C4-C10 carboxylic acid ester is a fluorinated carboxylic acid ester; the nitrile compound includes an unsaturated nitrile; the unsaturated nitrile includes at least one of an unsaturated mononitrile compound and a fluorinated derivative thereof, an unsaturated polynitrile compound and a fluorinated derivative thereof; based on the total mass of the electrolyte, the total mass proportion of the fluorinated carboxylic acid ester and the unsaturated nitrile is recorded as D%, and D satisfies: 0≤D≤30, for example, it can be 0, 1%, 2%, 5%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30% or any point value in the range of the above two point values. The fluorinated carboxylic acid ester includes at least one of difluoroethyl acetate, trifluoroethyl acetate, ethyl 3-fluoropropionate, and ethyl 3,3,3-trifluoropropionate; and / or, the unsaturated nitrile includes at least one of acrylonitrile, crotononitrile, trans-butenedinitrile, and trans-hexenedinitrile.

[0038] Fluorinated carboxylates in carboxylates have strong antioxidant properties due to the substitution of fluorine atoms, which can significantly improve the overall antioxidant properties of the electrolyte and reduce the oxidative deterioration of the electrolyte; unsaturated nitriles in nitrile compounds not only have good antioxidant properties, but can also participate in the formation of SEI film on the surface of the electrode, avoiding direct contact between the electrolyte and the electrode active material and reducing the occurrence of side reactions. However, fluorinated carboxylates and unsaturated nitriles usually have high viscosities. When their content in the electrolyte is too high, the overall viscosity of the electrolyte will increase significantly, thereby reducing the conductivity of the electrolyte, and lithium ions cannot be normally transmitted in the electrolyte, which easily causes lithium precipitation problems on the electrode surface, resulting in reduced battery performance. Since the surface of the pole piece is provided with protrusions and depressions, the uneven texture of the pole piece surface not only provides more penetration channels for the electrolyte, optimizes the transmission performance of the electrolyte, and to a certain extent alleviates the problems of increased electrolyte viscosity and decreased conductivity caused by high contents of fluorocarboxylates and unsaturated nitriles, but also helps to guide the uniform distribution and transmission of lithium ions on the surface of the pole piece, reducing the risk of lithium precipitation. Therefore, further adjusting the total mass proportion of the fluorocarboxylates and the unsaturated nitriles to meet the above range, and coordinating the arrangement of the depressions and protrusions on the surface of the pole piece, can improve the high-voltage cycle performance of the battery while taking into account the fast charging performance of the battery.

[0039] In some embodiments, the electrolyte includes fluorobenzene compounds; based on the total mass of the electrolyte, the mass proportion of the fluorobenzene compounds is recorded as E%; E satisfies: 2≤E≤20, for example, it can be 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20% or any point value in the range of the above two point values. Preferably, the fluorobenzene compounds include fluorobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, 1,2,3,4-tetrafluorobenzene, 1,2,3,5-tetrafluorobenzene, 1,2,4,5-tetrafluorobenzene, pentafluorobenzene, perfluorobenzene, and at least one of the fluorinated aromatic compounds of fluorobenzene listed above.

[0040] Although the protrusions and depressions are set on the surface of the pole piece, the specific surface area of ​​the pole piece is improved and the rate of lithium ion embedding and detaching from the pole piece is increased, but the compaction density of the pole piece is also high, and the pores between materials are relatively reduced, which is not conducive to the infiltration of the electrolyte and limits the further improvement of the battery's fast charging performance. Fluorobenzene compounds are aromatic fluorinated alkanes with strong aromaticity. The aromatic structure in fluorobenzene compounds can form a π-π stacking effect with the electrode structure, making it easier to enter the pole piece. When fluorobenzene compounds are introduced as one of the solvents in the electrolyte, the wettability of the electrolyte to the pole piece can be significantly improved, accelerating the embedding and detachment of lithium ions in the pole piece, reducing lithium precipitation on the electrode surface, and further optimizing the battery's fast charging performance. However, fluorobenzene compounds have low polarity and low solubility in lithium salts. If the content is too high, lithium salts will be precipitated. When the content of fluorobenzene compounds is adjusted within the above range, the problem of lithium salt precipitation caused by excessive content of fluorobenzene compounds can be avoided, thereby ensuring that the fluorobenzene compounds can play a role and do not deteriorate other battery properties (such as cycle performance and safety, etc.).

[0041] In some embodiments, the electrolyte includes a lithium salt; based on the total mass of the electrolyte, the mass proportion of the lithium salt is 5%-20%, for example, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 19%, 20%, or any point value in the range of any two of the above points. The lithium salt includes a lithium-containing inorganic salt and / or a lithium-containing organic salt.

[0042] In some embodiments, the lithium-containing inorganic salt includes at least one of LiPF6, LiBF4, and LiPO2F2.

[0043] In some embodiments, the lithium-containing organic salt includes at least one of LiBOB, LiODFP, LiODFB, LiTFSI, LiFSI, and LiDTI.

[0044] Lithium ions are the main medium for transmission between the positive and negative electrodes of lithium batteries, and their content is directly related to battery performance. Especially in battery systems that require fast charging and discharging, adjusting the lithium salt content to meet the above range can avoid the increase in electrolyte viscosity that may occur when the lithium salt content is too high, affecting the transmission of lithium ions in the electrolyte and even causing lithium precipitation problems; and avoid the reduction of battery fast charging performance and energy density when the lithium salt content is too low, which affects the battery cycle life.

[0045] It should be noted that the mass proportion of carboxylic acid esters (A), the mass proportion of nitrile compounds (B), the mass proportion of propyl propionate, the mass proportion of difluoroethyl acetate, the mass proportion of fluorocarboxylic acid esters, the mass proportion of unsaturated nitriles, and the mass proportion of fluorobenzene compounds (E) in the present invention can all be measured by gas chromatography-mass spectrometry (GCMS).

[0046] In some embodiments, the electrolyte includes a carbonate solvent, and the carbonate solvent includes one or more of ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and methyl propyl carbonate (MPC).

[0047] In some embodiments, the positive electrode active material layer further includes a positive electrode active material, a positive electrode conductor and a positive electrode binder.

[0048] In some embodiments, the mass percentage of each component in the positive electrode active material layer is: 90wt%-99.2wt% of positive electrode active material, 0.4wt%-5wt% of positive electrode conductor, and 0.4wt%-5wt% of positive electrode binder.

[0049] In some embodiments, the positive electrode active material is selected from one or more of transition metal lithium oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium manganese oxide, and lithium-rich lithium manganese oxide; the chemical formula of the transition metal lithium oxide is Li (1+x) Ni y Co z M (1-y-z) O2, wherein -0.1≤x≤1; 0≤y≤1, 0≤z≤1, and 0≤y+z≤1; wherein M is one or more of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo, and Zr. There is no specific limitation on the positive electrode conductive agent, for example, conventional conductive agents in the art may be used, including but not limited to one or more of acetylene black, conductive carbon black, Ketjen black, conductive graphite, carbon nanotubes, conductive carbon fibers, and graphene. There is no specific limitation on the positive electrode binder, for example, conventional binders in the art may be used, including but not limited to one or more of polyvinylidene fluoride, polytetrafluoroethylene, sodium carboxymethyl cellulose, styrene-butadiene rubber, and polyethylene oxide.

[0050] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer coated on one or both sides of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material, a negative electrode conductor and a negative electrode binder.

[0051] In some embodiments, the mass percentage of each component in the negative electrode active material layer is: 90wt%-99.2wt% of negative electrode active material, 0.3wt%-5wt% of negative electrode conductor, and 0.5wt%-5wt% of negative electrode binder.

[0052] In some embodiments, the negative electrode active material includes a composite material of one or more of artificial graphite, natural graphite, hard carbon, soft carbon, silicon carbon, silicon oxygen, nano silicon, and silicon alloy. The types of negative electrode conductive agent and negative electrode binder are not specifically limited, and conventional conductive agent and binder types in the art can be selected. The types of negative electrode conductive agent include but are not limited to at least one of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes, and metal powder. Negative electrode binders include butadiene styrene rubber emulsion, polytetrafluoroethylene emulsion, sodium carboxymethyl cellulose, sodium alginate, polyvinyl alcohol, polyacrylic acid, lithium polyacrylate, sodium polyacrylate, and carboxylated chitosan.

[0053] In the present invention, the type of the diaphragm is not specifically limited. For example, conventional lithium-ion battery diaphragms in the art can be selected, including but not limited to woven membranes, non-woven membranes (non-woven fabrics), microporous membranes, composite membranes, diaphragm paper, rolled membranes, polyethylene microporous membranes, polypropylene microporous membranes, etc.

[0054] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0055] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0056] The present invention is described in detail below in conjunction with specific embodiments, which are used to understand but not to limit the present invention.

[0057] Example 1-1: 1. Preparation of positive electrode Lithium cobalt oxide, conductive agent (a mixture of conductive carbon black and carbon nanotubes), and PVDF were placed in NMP at a mass ratio of 97.60:1.35:1.05 and stirred evenly to prepare a positive electrode slurry; the positive electrode slurry was evenly coated on the front and back sides of a 9μm aluminum foil, and the coating surface density was 0.01704g / cm 2 ; After drying and roller pressing (roller pressing compaction is 4.2 g / cm 2) treatment was performed to obtain a positive electrode sheet with a single-side thickness of the positive electrode active material layer of 90 μm; the slit positive electrode sheet was subjected to convex processing using a special roller containing convex portions, wherein the height of the convex portions was 20 μm, the diameter was 2 mm, and the average convex portion spacing was 3 mm.

[0058] 2. Preparation of negative electrode sheet Silicon-containing artificial graphite, conductive carbon black, styrene-butadiene rubber and sodium carboxymethyl cellulose are placed in deionized water in a mass ratio of 97.2:0.5:1.3:1, wherein the silicon content in the silicon-containing artificial graphite is 10%; the above slurry is stirred evenly to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on a negative electrode current collector, and dried, rolled and slid in sequence to obtain a negative electrode sheet.

[0059] 3. Preparation of electrolyte In a glove box filled with argon (water <1 ppm, oxygen <1 ppm), ethylene carbonate (EC), diethyl carbonate (DEC), and propyl propionate (PP) were mixed into a uniform solvent, and LiPF6 and fluoroacetonitrile were slowly added at a mass ratio of 14% and 15% based on the total mass of the electrolyte. After stirring evenly, the desired lithium-ion battery electrolyte was obtained. Based on the total mass of the electrolyte, the mass ratio of PP was 45%. The total amount of EC and DEC can be calculated, and the mass ratio of the two is 1:1.

[0060] 4. Preparation of lithium-ion batteries The cut positive electrode sheet, separator, and negative electrode sheet are stacked in sequence and wound into a wound-type battery cell. The battery cell is packaged, injected, formed, and sealed to obtain a lithium-ion battery. The separator is a 9 μm thick substrate + alumina ceramic + PVDF adhesive separator.

[0061] Performance Testing (1) 25℃ cycle performance test The batteries prepared in the embodiments and comparative examples were charged and discharged for 500 cycles at 25°C at a rate of 1C within the charge and discharge cut-off voltage range (3.0V-4.5V). The discharge capacity in the first week of the test was x1 mAh, and the thickness of the test battery was y1; the discharge capacity in the 500th week was x2 mAh, and the thickness of the battery after the 500th week was y2; the cycle capacity retention rate at the 500th week was R1=x2 / x1; and the battery thickness expansion rate at the 500th week was H1=(y2-y1) / y1.

[0062] (2) 45℃ cycle performance test The batteries prepared in the embodiments and comparative examples were charged and discharged for 500 cycles at 45°C and at a rate of 1C within the charge and discharge cut-off voltage range (3.0V-4.5V). The discharge capacity in the first week of the test was x3 mAh, and the thickness of the test battery was y3; the discharge capacity in the 500th week was x4 mAh, and the thickness of the battery after the 500th week was y4; the cycle capacity retention rate at the 500th week was R2=x4 / x3; and the battery thickness expansion rate at the 500th week was H2=(y4-y3) / y3.

[0063] (3) 25℃ 4.7V cycle performance test The batteries prepared in the embodiments and comparative examples were charged and discharged for 300 cycles at 25°C at a rate of 1C within a charge and discharge cut-off voltage range (3.0V-4.7V). The discharge capacity in the first week of the test was x1 mAh, and the thickness of the test battery was y1; the discharge capacity in the 300th week was x2 mAh, and the thickness of the battery after the 300th week was y2; the cycle capacity retention rate in the 300th week was R=x2 / x1; and the battery thickness expansion rate in the 300th week was H=(y2-y1) / y1.

[0064] (4) Analysis test The batteries prepared in the examples and comparative examples were charged to 4.5V at 3C constant current and constant voltage at 25°C, with a cut-off current of 0.05C, and then discharged to 3.0V at 0.5C constant current. After 20 cycles, the batteries were fully dissected and lithium deposition was observed, wherein the degree of lithium deposition is as follows from light to heavy: no lithium deposition, slight lithium deposition, lithium deposition and severe lithium deposition.

[0065] The examples 1-3 and comparative examples 1-5 are carried out with reference to the example 1-1, and the main differences are shown in Table 1. Among them, in the example 1 group, the height (H) of the first protrusion and / or the diameter (R) of the first protrusion are changed, and the ratio of H / R is changed. In the example 2 group, the mass proportion (A) of the carboxylic acid ester in the electrolyte is changed. In the example 3 group, the mass proportion (B) of the nitrile compound in the electrolyte is changed. In the comparative example 1, the ratio of H / R is too small and is not within the protection scope of the present invention. In the comparative example 2, the ratio of H / R is too large and is not within the protection scope of the present invention. In the comparative example 3, the mass proportion of the carboxylic acid ester in the electrolyte is too small and is not within the protection scope of the present invention. In the comparative example 4, the mass proportion of the nitrile compound in the electrolyte is too large and is not within the protection scope of the present invention. Comparative example 5 is a pole piece that is not embossed.

[0066] Table 1 Note: "*" indicates that the corresponding parameter in this embodiment or comparative example is the same as that in Example 1-1. " / " indicates that the corresponding parameter was not tested.

[0067] The larger the H / R ratio, the sharper the shape of the pole piece embossing, and the more likely the pole piece deformation during the battery charging and discharging process will cause damage and rupture of the pole piece structure; the smaller the H / R ratio, the flatter the shape of the pole piece embossing, and the relatively shallow embossing marks, which cannot play the advantages and functions of the embossing. When the content of carboxylic acid ester in the electrolyte is too high, the antioxidant property of the electrolyte will be reduced; when the content of nitrile compounds is too high, the interface stability of the battery negative electrode is poor; and when the content of carboxylic acid ester and nitrile compounds is too low, the effect of increasing the conductivity of the electrolyte and reducing the viscosity of the electrolyte cannot be played, resulting in a decrease in battery performance. As can be seen from Table 1, the present invention can reduce lithium plating, improve the fast charging performance of the battery, and improve the battery cycle stability by adjusting H and R to meet: 0.2≤H / R≤80; A meets: 10≤A≤80; B meets: 3≤B≤30.

[0068] Example 4 was carried out with reference to Example 1-1, with the main differences shown in Table 2. In Example 4, the type of carboxylic acid ester was changed.

[0069] Table 2 It can be seen from Table 2 that selecting different types of carboxylates in the present invention can produce similar effects, and can improve the fast charging performance of the battery, enhance the cycle stability of the battery, and reduce lithium plating.

[0070] Example 5 was carried out with reference to Example 1-1, and the main differences are shown in Table 3. In Example 5, the type of nitrile compound was changed.

[0071] Table 3 It can be seen from Table 3 that selecting different nitrile compounds can achieve similar effects, and can improve the fast charging performance of the battery, enhance the battery cycle stability, and reduce lithium plating.

[0072] The sixth embodiment was carried out in accordance with the first embodiment, and the main differences are shown in Table 4. In the sixth embodiment, the convex portion processing was performed using a special roller with convex portions having different parameters, so that the average pitch of the first convex portions was changed.

[0073] Table 4 It can be seen from Table 4 that when the average spacing is too small, the pole piece is more likely to deform during the charge and discharge process of the battery, which can easily lead to damage and rupture of the pole piece structure and reduce battery performance; when the average spacing is too large, the embossing density on the pole piece surface is too small and the embossing effect cannot be fully exerted. When the average spacing of the first protrusion and the average spacing of the first depression meet the range of 0.5mm-8mm, the fast charging performance of the battery can be improved, the battery cycle stability can be enhanced, and lithium plating can be reduced.

[0074] Example 7 was carried out in accordance with Example 1-1, with the main differences shown in Table 5. In Example 7, difluoroethyl acetate (DFEA) was further added to the electrolyte, and the mass ratio C of propyl propionate (PP) to difluoroethyl acetate (DFEA) was changed.

[0075] Table 5 Note: “ / ” indicates that the corresponding parameter is not tested.

[0076] As shown in Table 5, the mass ratio C of PP to DFEA is too large, indicating that the mass ratio of DFEA in the electrolyte is too low, the worse the electrolyte oxidation resistance, the worse the battery performance, and at the same time, the value of C is too small, the electrolyte viscosity is too high, the lithium salt solubility is too low, lithium precipitation is serious, and the battery performance is further reduced. When C satisfies 1≤C≤10, the cycle performance of the battery under high voltage can be further improved, while taking into account the fast charging performance of the battery.

[0077] Example 8 was carried out in accordance with Example 7-1, and the main differences are shown in Table 6. In Example 8, the type of nitrile compound in the original electrolyte, fluoroacetonitrile, was replaced with trans-hexenedinitrile, and the total mass proportion of fluorocarboxylic acid ester (DFEA) and unsaturated nitrile (trans-hexenedinitrile) was changed to D%.

[0078] Table 6 As shown in Table 6, when the nitrile compound in the electrolyte is an unsaturated nitrile (trans-hexenedinitrile), the use of fluorinated carboxylic acid ester (DFEA) will further enhance the antioxidant property of the electrolyte. Combined with the electrode embossing process, it can further improve the high-voltage cycle performance of the battery while taking into account the fast charging performance of the battery. However, adding too much unsaturated nitrile and fluorinated carboxylic acid ester to the electrolyte will lead to excessive viscosity of the electrolyte and deteriorate battery performance.

[0079] Example 9 was carried out with reference to Example 8-1, with the main differences shown in Table 7. In Example 9, fluorobenzene (fluorobenzene compound) was further added to the electrolyte, and the mass proportion of fluorobenzene in the electrolyte was adjusted to E%.

[0080] Table 7 It can be seen from Table 7 that when fluorobenzene compounds are further added to the electrolyte and E satisfies 2≤E≤10, lithium plating on the electrode surface can be further reduced, the fast charging performance of the battery can be optimized, and the cycle stability of the battery can be improved; avoiding E being too large, which will deteriorate the solubility of the lithium salt and reduce the battery performance.

[0081] It should be noted that, in this article, the terms "comprise", "include" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be pointed out that the scope of the methods and devices in the embodiments of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.

[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A lithium ion battery, characterized in that: The battery comprises a positive electrode sheet, a negative electrode sheet and an electrolyte; In the thickness direction of the positive electrode sheet, the positive electrode sheet includes a first surface and a second surface arranged opposite to each other, the first surface is provided with a plurality of first protrusions at intervals, and the second surface is provided with a plurality of first recesses correspondingly; the height of the first protrusion is recorded as H μm, the diameter of the first protrusion is recorded as R mm, and H and R satisfy: 0.2≤H / R≤80; The electrolyte includes carboxylic acid ester, and the mass proportion of the carboxylic acid ester is denoted as A% based on the total mass of the electrolyte; A satisfies: 10≤A≤80; The electrolyte includes nitrile compounds, and the mass proportion of the nitrile compounds, based on the total mass of the electrolyte, is denoted as B%; B satisfies: 3≤B≤30.

2. The battery according to claim 1, characterized in that H and R satisfy: 0.75≤H / R≤20; and / or, the carboxylic acid ester comprises at least one of a C4-C10 carboxylic acid ester and a fluorinated derivative thereof; And / or, the nitrile compound includes at least one of a C2-C10 mononitrile compound and a fluorinated derivative thereof, a C2-C10 polynitrile compound and a fluorinated derivative thereof.

3. The battery according to claim 2, characterized in that The carboxylic acid ester comprises at least one of ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, and difluoroethyl acetate; And / or, the nitrile compound includes acetonitrile, propionitrile, butyronitrile, isobutyronitrile, malononitrile, succinonitrile, glutaronitrile, adiponitrile, 1,3,6-hexanetrinitrile, benzonitrile, acrylonitrile, crotononitrile, trans-butenedinitrile, trans-hexenedinitrile, 1,2-bis(cyanoethoxy)ethane, and at least one of the fluorinated derivatives of the nitrile compound.

4. The battery according to claim 3, characterized in that The carboxylic acid esters include propyl propionate and difluoroethyl acetate; In the electrolyte, the mass ratio of propyl propionate to difluoroethyl acetate is denoted as C, and C satisfies: 1≤C≤10.

5. The battery according to claim 2, characterized in that The fluorinated derivative of the C4-C10 carboxylic acid ester is a fluorinated carboxylic acid ester; And / or, the nitrile compound includes unsaturated nitrile; the unsaturated nitrile includes unsaturated mononitrile compound and fluorinated derivatives thereof, unsaturated polynitrile compound and fluorinated derivatives thereof.

6. The battery according to claim 5, characterized in that Based on the total mass of the electrolyte, the total mass proportion of the fluorocarboxylic acid ester and the unsaturated nitrile is recorded as D%, and D satisfies: 0≤D≤30; And / or, the fluorocarboxylic acid ester includes at least one of difluoroethyl acetate, trifluoroethyl acetate, ethyl 3-fluoropropionate, and ethyl 3,3,3-trifluoropropionate; And / or, the unsaturated nitrile includes at least one of acrylonitrile, crotononitrile, trans-butenedinitrile and trans-hexenedinitrile.

7. The battery according to any one of claims 1 to 6, characterized in that: The first protrusion and / or the first depression satisfies at least one of the following conditions: (a) the average spacing between adjacent first protrusions is 0.5 mm to 8 mm; and / or the average spacing between adjacent first depressions is 0.5 mm to 8 mm; (b) the height of the first protrusion is 3 μm-100 μm; and / or the depth of the first depression is 3 μm-100 μm; (c) the diameter of the first protrusion is 0.5 mm to 4 mm; and / or the diameter of the first depression is 0.5 mm to 4 mm.

8. The battery according to claim 7, characterized in that The first protrusion and / or the first depression satisfies at least one of the following conditions: (a) the average spacing between adjacent first protrusions is 1 mm to 4 mm; and / or the average spacing between adjacent first depressions is 1 mm to 4 mm; (b) the height of the first protrusion is 5 μm-80 μm; and / or the depth of the first depression is 5 μm-80 μm; (c) the diameter of the first protrusion is 1 mm to 3 mm; and / or the diameter of the first depression is 1 mm to 3 mm.

9. The battery according to any one of claims 1 to 6, characterized in that: The electrolyte includes a fluorobenzene compound; Based on the total mass of the electrolyte, the mass proportion of the fluorobenzene compound is denoted as E%; and E satisfies: 2≤E≤20.

10. The battery according to claim 9, characterized in that The fluorobenzene compounds include fluorobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, 1,2,3,4-tetrafluorobenzene, 1,2,3,5-tetrafluorobenzene, 1,2,4,5-tetrafluorobenzene, pentafluorobenzene, perfluorobenzene, and at least one of the fluorinated aromatic compounds of the fluorobenzenes.

11. The battery according to any one of claims 1 to 6, characterized in that: The electrolyte includes a lithium salt; the mass of the lithium salt accounts for 5%-20% of the total mass of the electrolyte; The lithium salt includes a lithium-containing inorganic salt and / or a lithium-containing organic salt.

12. The battery according to claim 11, characterized in that The lithium-containing inorganic salt includes at least one of LiPF6, LiBF4, and LiPO2F2; And / or, the lithium-containing organic salt includes at least one of LiBOB, LiODFP, LiODFB, LiTFSI, LiFSI, and LiDTI.

Citation Information

Patent Citations

  • Pole piece and battery cell

    CN107681116A

  • Electrochemical device and electronic device

    CN113921909A

  • Battery pole piece, preparation method thereof and lithium ion battery

    CN114843438A

  • Battery cell, battery and electric device

    CN114843624A

  • Electrolyte with ultra-wide temperature application range and electrochemical device thereof

    CN116365040A

Cited By

  • Battery and electric device

    CN120165038A

  • Battery and electric apparatus

    EP4815094A1